Caregiver Strategies to Enhance Participation in Children With Autism Spectrum Disorder. (October 2018) - Schiavone, Nicole; Szczepanik, David; Koutras, John; Pfeiffer, Beth; Slugg, Laura
Participation is necessary for childhood development, however, children with disabilities participate in fewer activities than their nondisabled peers. This study identified strategies caregivers use to increase participation in home- and community-based activities for children with autism spectrum disorder. Survey responses of 44 caregivers were analyzed through open and axial coding to develop a central theme and five broad themes. Caregiver strategies which produce a participation outcome fell into five themes: (a) adapters/facilitators, (b) pragmatic considerations, (c) social reframing, (d) sensory adjustments, and (e) desperate measures. Nonproductive strategies were identified where the child did not participate in the activity. Adaptations/facilitators were more likely used in the home, whereas community-based strategies were more often pragmatic considerations. Nonproductive strategies occurred more frequently in the community. When evaluating a child's participation, occupational therapy (OT) practitioners should take into consideration the context of the activity to identify appropriate and helpful strategies.